IMPLEMENTASI BAHASA PEMPROGRAMAN PHP DAN MYSQL DALAM PERANCANGAN APLIKASI TICKET CENTER RESERVATION PO. NPM - Hardiyanti Putri, Stefani; Aulia, Wizra (INTI Nusa Mandiri, 2025)
The rapid development of information technology today significantly impacts various sectors, including business, to compete more effectively. One of the important applications of technology is the development of a web-based information system for managing bus departure schedules and ticket reservations. This research aims to design and implement a web-based ticket reservation system for PO. NPM in Bukittinggi City, in order to improve efficiency and address data redundancy issues that occurred in the previous manual system. The system design method used is the Waterfall method. This system is built using PHP as the server-side programming language and MySQL as the database to store ticket reservation data and bus departure schedules. The result of this research is a web-based ticket reservation system that allows passengers to book tickets online without having to visit the ticket counter. The implementation of the web-based information system at PO. NPM can improve passenger comfort, operational efficiency, and better data management. This system also contributes to improving service quality and reducing the potential for errors in data processing.